A mortality risk analysis for OSHA's COVID-19 emergency regulations - James Broughel; Andrew Baxter (Journal of Risk and Financial Management, 2022)
In 2021, the Occupational Safety and Health Administration (OSHA) issued two emergency temporary standard regulations related to COVID-19 hazards in US workplaces. One regulation covered healthcare sector workers, while the second regulation would have covered workers at firms with 100 or more employees. This paper conducts an original mortality risk analysis for these regulations. Mortality risk analysis evaluates the increase or decrease in expected mortality associated with a new policy, such as a rule or regulation, taking into account economic factors like lost income due to regulatory costs. If we accept OSHA's cost and health benefit estimates at face value, we find that the first regulation related to COVID-19 hazards in the healthcare sector reduces risk initially but increases risk over a longer time horizon. We find that the second regulation would reduce risk according to OSHA's main estimates but may not reduce risk after including some ancillary costs and adjusting the agency's prevented hospitalizations estimate based on more reasonable assumptions. Moreover, OSHA's economic analysis for the two regulations in question does not purport to comprehensively evaluate costs; ergo, our mortality risk estimates probably underestimate countervailing mortality risks stemming from these regulations. We review some of OSHA's underlying assumptions that could change the outcomes of our mortality analysis. These estimates demonstrate that OSHA would benefit from more comprehensive consideration of costs in its economic analysis.
Keywords: 650; mortality risk analysis; COVID-19; OSHA